2016
DOI: 10.1080/15389588.2016.1201205
|View full text |Cite
|
Sign up to set email alerts
|

Impairment due to alcohol, tetrahydrocannabinol, and benzodiazepines in impaired drivers compared to experimental studies

Abstract: Fewer test results indicated impairment in experimental studies compared to impaired drivers in real life when influenced by similar blood concentrations of either ethanol, THC, or benzodiazepines. In addition, a comparable relationship between drug concentration and impairment was seen for both experimental studies and real-life cases. We believe that the present study strengthens the background for using experimental studies to establish fixed concentration limits for drunk and drugged drivers, but experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
0
1
1
Order By: Relevance
“…The conclusion of the CTI is found to reveal impairment to a higher degree than any of the single subtests (104) and that can explain the higher degree of detected clinical impairment. These results are in accordance with a previous study which found that fewer subjects demonstrate impairment in an experimental setting compared to real-life drug use settings (204). It can also be argued that the physicians performing the CTI might be biased by a subjective expected impairment in a population of suspected drugged drivers, or that the clinical impairment seen in low concentration (low specificity) in the real-life setting is caused by the stress associated with being apprehended by the police and tested by a physician.…”
Section: 4)supporting
confidence: 93%
See 1 more Smart Citation
“…The conclusion of the CTI is found to reveal impairment to a higher degree than any of the single subtests (104) and that can explain the higher degree of detected clinical impairment. These results are in accordance with a previous study which found that fewer subjects demonstrate impairment in an experimental setting compared to real-life drug use settings (204). It can also be argued that the physicians performing the CTI might be biased by a subjective expected impairment in a population of suspected drugged drivers, or that the clinical impairment seen in low concentration (low specificity) in the real-life setting is caused by the stress associated with being apprehended by the police and tested by a physician.…”
Section: 4)supporting
confidence: 93%
“…The possibility of acute tolerance is further discussed under Aim 1c. A study that investigated ethanol showed that 70% of drivers tested with the CTI were judged to be impaired with BAC in the range 0.2-0.5 g/kg, while 83% were concluded as impaired with BAC in the range 0.5-1.2 g/kg (204). This is also a considerably higher occurrence than in the present study and could be explained by different populations.…”
Section: 4)contrasting
confidence: 69%
“…Vi har vist at det er god overensstemmelse mellom utfall på kognitive og psykomotoriske ferdigheter og konsentrasjonen av THC i blodet (14)(15)(16)…”
Section: Bilkjøring Og Førerkortunclassified